EVALUASI TERHADAP PERLAKUAN AKUNTANSI ATAS PENDAPATAN DAN BEBAN PADA PT GMJ GADAI PERIODE 2022-2024 - Imariska Ekka Putri (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The purpose of this scientific paper is to convey the accounting treatment of income and expenses at PT GMJ Gadai based on the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). The analysis was carried out on the company's financial statements for the period 2022 to 2024, which focused on the recognition, measurement, and presentation of income and expenses. This study uses a qualitative descriptive research method that uses primary and secondary data types obtained by data collection techniques using interview methods, documentation, observation, and literature studies. The results of this study indicate that PT GMJ Gadai Umum has generally applied accounting principles according to SAK ETAP in recognizing income and expenses, but there are still some things that are not in accordance with the classification of expenses, consistency of disclosure, and application of the accrual basis that still need adjustment. Therefore, recommendations are given to improve the quality of the company's financial reporting through the implementation of a more comprehensive accounting system and training employees about SAK ETAP.